Exploring large data over wide area networks - Hereld, M.; Insley, J. A.; Olson, E. C.; Papka, M. E.; Vishwanath, V.; Norman, M. L.; Wagner, R. (2011 IEEE Symposium on Large Data Analysis and Visualization, 2011)
Simulations running on the top supercomputers are routinely producing multi-terabyte data sets. Enabling scientists, at their home institutions, to analyze, visualize and interact with these data sets as they are produced is imperative to the scientific discovery process. We report on interactive visualizations of large simulations performed on Kraken at the National Institute for Computational Sciences using the parallel cosmology code Enzo, with grid sizes ranging from 1024 3 to 6400 3 . In addition to the asynchronous rendering of over 570 timesteps of a 4096 3 simulation (150 TB in total), we developed the ability to stream the rendering result to multipanel display walls, with full interactive control of the renderer(s).